CITIZENSHIP CHARACTER FORMATION THROUGH PANCASILA VALUES IN STUDENTS OF THE KAMPUNG BHARU MALAYSIA LEARNING STUDY SCHOOL - Miftha Huljannah; Ryan Taufika; Zulkifli Amin; Fitri Amaliah; Heru Sanjaya; Juliaman Siahaan (Program Pascasarjana UIN Sumatera Utara, 2026)
An important element in the formation of students' civic character lies in the extent to which Pancasila values can be internalized in a contextual and meaningful learning process. The purpose of this study is to determine the extent to which the internalization of Pancasila values is able to shape the civic character of students at the Kampung Bharu Malaysia Learning Center. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of teachers and sixth grade students. The results of the study indicate that the process of forming civic character is carried out through habituation, role models, and value-based learning activities that emphasize aspects of religious values, discipline, and nationalism. This study found that the internalization of Pancasila values can create a pleasant learning atmosphere and is oriented towards strengthening character. This strategy has proven effective in strengthening the sense of nationalism of Indonesian students abroad, and is applied continuously in other non-formal education programs to improve the quality of civic character formation.